The effect of dispersion of dirt particles in oils on their electrical conductivity and mechanical strength - Ventsel, Ye.; Shchukin, O.; Orel, O.; Yevtushenko, A. (Problems of Tribology, 2019)
It has been shown theoretically and confirmed experimentally that the dispersion of dirt particles found in engine oils and working fluids affects significantly their physical properties. In particular, it has been established that if dirt particles are artificially dispersed in a lubricant, its electrical conductivity increases. This, in turn, is expected to lead to a decrease in the share of electrostatic wear of the tribo units. Such particles are also able to increase the mechanical strength (surface tension) of lubricating films, that is, to make the boundary layers more durable, due to which we can expect a decrease in wear of tribo units. In this case, the thermal conductivity of oil lubricating films with highly dispersed dirt particles does not change.